"The bucket of gold at the end of the rainbow": personal experiences of hope after acquired brain injury. Issue 25 (4th December 2022) - Bellon, Michelle; Kelley, Jasmin; Fisher, Alinka
Abstract: Purpose: To investigate personal experiences of, and factors influencing hope following Acquired Brain Injury (ABI). Methods: A qualitative phenomenological approach was adopted consisting of semi-structured interviews with 15 adults with ABI. Interviews were transcribed and analysed using thematic analysis, and the Social Ecological Model (SEM) applied as a guiding framework to discuss findings and implications for policy and practice. Results: Five themes emerged: the importance of hope, changes in hope over time, the connection between hope and positivity, factors influencing hope and the importance of fostering hope. Participants reported varying experiences, with increased levels of hope influenced by: faith; supportive networks and professionals; goals; experiencing progress; having something to look forward to; and seeing others achieve. Professional attitudes were reported to either foster or negatively impact hope after brain injury. Conclusions: These findings suggest that hope can play an important and often essential role in the lives of people with ABI. Factors influencing experiences of hope are organised against a SEM framework, identifying intrapersonal, interpersonal, institutional, community, and state and national implications for policy, professional practice and research. Implications for rehabilitation: Hope plays a critical role in the lives of people following acquired brain injury. Factors which positively influence hope include faith, supportive networks, goals, experiencing progress, and having something to look forward to. Professionals can impact an individual's experience of hope through person-centred and supportive therapeutic relationships.